URUF DAN IMPLIKASINYA TERHADAP KEDUDUKAN NAFKAH ISTRI KARIR - Harwis Alimuddin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
The law should be changed because of the changes in the public's ‘urf. Changes to the law are built on the basis of benefit, needs and principles of Shari'a which always adjust to the conditions of society. In order to maintain the balance principle of the rights and obligations of a husband and wife, the rights and obligations of a husband should be adapted to the prevailing development of the ‘urf. After being adapted to the ‘urf, the results of this research indicated that the career wife’s living is not only obliged to the husband. Further more, the wife who has a career should participate in family income as a partner for her husband.